Mini-sondage au Mali - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Dramane Coulibaly, président du comité des lecteurs du Centre de documentation d'Action Jeunesse Rurale